THE IMPACT OF THE CORONAVIRUS PANDEMIC IN THE UK, THE US AND EU MEMBER STATES (IUS LAW Journal, 2025)
This paper, critically analyses how the coronavirus pandemic evolved as a contagious disease that became a menace to public health and culminated into the worst global crisis in this century. The paper exposes how the overburdened and underfunded health care system of the three jurisdictions was made vulnerable. Most governments took an unsystematic approach, by initially making effort to conceal the level of the virus severity, while others took proactive steps to block the spread due to their level of disaster risk preparedness. This paper exhibits the socio-economic impact of coronavirus outbreak and the numerous protective measures taken to contain the spread of the virus by the government and the resultant outcomes of those measures. The paper then provides insights into numerous government’s dilemma of saving citizens and the planet on the one hand and keeping the financial systems in motion on the other.
Keywords: coronavirus pandemic, public health, socio-economic impact, EU member states, government’s dilemma